Effect of the divertor configuration on the JET edge radial electric field. (1st December 2022) - Silva, C.; Solano, E.R.; Hillesheim, J.C.; Delabie, E.; Birkenmeier, G.; Gil, L.; Giroud, C.; Morales, R.B.; Nina, D.
Abstract: The role of the divertor configuration and divertor plasma physics on the L–H transition is poorly understood, leading to large uncertainties in predicting the L–H power threshold in future devices. This contribution reports on edge perpendicular plasma flow measurements by Doppler backscattering in JET L–H transition experiments with the outer divertor strike-point at different positions: horizontal target (HT), vertical target (VT), and in the corner configuration (between the HT and VTs). The edge perpendicular flow was found to be significantly affected by changes in the divertor configuration in the region inside the separatrix. Our results do not show evidence for the existence of a critical edge flow shear needed to achieve H-mode for different divertor configurations, with a larger shear observed for the VT configuration. No significant change in the shear flow and in the density fluctuation level is measured preceding the L–H transition in the region just inside the separatrix. The dynamics of the L–H transitions are also influenced by the divertor configuration with divertor oscillations (DOs) observed only in the HT configuration. Interestingly, DOs are associated with marked changes in the edge perpendicular flow around the separatrix.